An Agents’ Model Using Ontologies and Web Services for Creating and Managing Virtual Enterprises - Mahmoud, Brahimi (Université de M'sila, 2018)
Currently, the economic competition has become very tough where successful companies find themselves obliged to develop their organizations and diversify their work strategies. Thereby, virtual enterprises concept imposes itself and overcomes geographical constraints by allowing companies to cooperate and address their shortcomings through exchanging their services and skills. The present paper proposes a virtual enterprise model based on the use of agents endorsed by the use of ontologies and web services. The coupling of these concepts allows reducing the high costs associated with the use of technology and improves flexibility and intelligence both in the negotiation process through the selection of the best partners, and in the managing process by ensuring the effective cooperation between partners.
Keywords: Virtual Enterprises, Agents, Ontologies, Web Services, Negotiation, FIPA-ACL